SKIPJACK TUNA FISHING SEASON AND ITS RELATIONSHIP WITH OCEANOGRAPHIC CONDITIONS IN PALABUHANRATU WATERS, WEST JAVA - NURANI, TRI WIJI; WAHYUNINGRUM, PRIHATIN IKA; IQBAL, MUHAMMAD; KHOERUNNISA, NURANI; PRATAMA, GILAR BUDI; WIDIANTI, ELVANRI ANGGI; KURNIAWAN, MUHAMMAD FIKRI (Malaysian Applied Biology, 2022)
Skipjack tuna (Katsuwonus pelamis) is the main catch species in Indonesian Palabuhanratu waters. The dynamics of skipjack fishing areas are influenced by oceanographic parameters such as sea surface temperature and chlorophyll-a concentration. This study aims to predict the skipjack fishing season, analyze the dynamics of oceanographic conditions, especially the distribution of sea surface temperature and the distribution of chlorophyll-a, and determine the relationship between skipjack fishing season and the dynamics of the distribution of sea surface temperature and the distribution of chlorophyll-a in the waters of Palabuhanratu, West Java. Catch per unit effort analysis was used to determine the fishing season index, while the dynamics of sea surface temperature and distribution of chlorophyll-a were analyzed from MODIS image data. The results showed that skipjack fishing season in Palabuhanratu waters was from July to November. Monthly sea surface temperatures range from 26-30℃ with an average value of 29℃. The distribution value of chlorophyll-a concentration ranged from 0.09 mg/m3 to 0.51 mg/m3 with an average value of 0.23 mg/m3. Skipjack tuna production tends to increase when sea surface temperatures are low and chlorophyll-a concentrations increase.